"Raisin Bun"‐Like Nanocomposites of Palladium Clusters and Porphyrin for Superior Formic Acid Oxidation. (10th April 2013) - Wang, Xiuxin; Yang, Jiandong; Yin, Huajie; Song, Rui; Tang, Zhiyong
<x xml:space="preserve">Abstract</x> A novel "raisin bun"‐like nanocomposite, where Pd clusters are embedded in porphyrin matrix, is developed as a promising electrocatalyst. Thanks to the synergy between the Pd clusters and the porphyrin matrix, this composite exhibits a low oxidation potential, high mass activity and excellent stability toward electrochemical oxidation of formic acid, which opens new routes for the design of high‐performance catalysts in fuel cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>